КОНТЕКСТЛИК АНТОНИМЛЕРДИҢ КОНТРАСТ ЎАЗЫЙПАСЫ - Кдырбаева, У.К. (FAN va JAMIYAT, 2024)
The article studied contextual antonyms and their features in the language of the Karakalpak heroic epics (“Alpamis”, “Kirik kiz” and “Edige”) and conducts a lingvopoetic analysis.